2021
DOI: 10.3390/ma14247799
|View full text |Cite
|
Sign up to set email alerts
|

The Studies on α-Pinene Oxidation over the TS-1. The Influence of the Temperature, Reaction Time, Titanium and Catalyst Content

Abstract: The work presents the results of studies on α-pinene oxidation over the TS-1 catalysts with different Ti content (in wt%): TS-1_1 (9.92), TS-1_2 (5.42), TS-1_3 (3.39) and TS-1_4 (3.08). No solvent was used in the oxidation studies, and molecular oxygen was used as the oxidizing agent. The effect of titanium content in the TS-1 catalyst, temperature, reaction time and amount of the catalyst in the reaction mixture on the conversion of α-pinene and the selectivities of appropriate products was investigated. It w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 46 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…The authors claimed that the catalytic system works without the requirement of additives or ligand. [19] Agnieszka Wróblewska et al reported titanium-silicalite (TS-1) catalysts for the oxidation of 𝛼-pinene [20,21] In one of the study, this research group revealed the autooxidation of 𝛼-pinene catalyzed by TS-1 with different titanium contents and achieved a conversion of 41.81 mol.% with a selectivity of 30.25 mol.% at 80 °C in 24 h under air atmosphere without the use of any organic solvents. The catalyst TS-1 exhibited autooxidation, isomerization and hydration of 𝛼-pinene and resulted in the respective products such as 𝛼-pinene oxide, campholenic aldehyde/carveol and 1,2-pinane diol.…”
Section: Heterogeneous Catalytic Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The authors claimed that the catalytic system works without the requirement of additives or ligand. [19] Agnieszka Wróblewska et al reported titanium-silicalite (TS-1) catalysts for the oxidation of 𝛼-pinene [20,21] In one of the study, this research group revealed the autooxidation of 𝛼-pinene catalyzed by TS-1 with different titanium contents and achieved a conversion of 41.81 mol.% with a selectivity of 30.25 mol.% at 80 °C in 24 h under air atmosphere without the use of any organic solvents. The catalyst TS-1 exhibited autooxidation, isomerization and hydration of 𝛼-pinene and resulted in the respective products such as 𝛼-pinene oxide, campholenic aldehyde/carveol and 1,2-pinane diol.…”
Section: Heterogeneous Catalytic Systemmentioning
confidence: 99%
“…Using this heterogeneous catalyst (0.5 wt.%), 40 mol.% conversion of 𝛼-pinene was achieved with 35 mol.% selectivity of 𝛼-pinene oxide at 100 °C in 2 h. The reported catalytic system is low-cost heterogeneous catalyst derived from the effective management of waste biomass. [20] Recently, in 2023, the same group reported porous ZSM-5 zeolites with different aluminium content as an active catalyst with oxygen. The catalytic efficiency was tested for the epoxidation of 𝛼 -pinene and observed 49 mol.% conversion with 28 mol.% selectivity of 𝛼-pinene oxide at 95 °C in 6 h. The catalytic system has the advantage of simple post-work process due to the avoidance of liquid oxidant such as hydrogen peroxide.…”
Section: Heterogeneous Catalytic Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…These compounds are readily used in the cosmetic and food industries, as well as in medicine as raw materials for obtaining perfumes, flavors, pharmaceuticals, and vitamins [38][39][40]. α-Pinene derivatives include such compounds as α-pinene oxide, campholenic aldehyde, L-carveol, verbenol, verbenone, trans-pinocarveol, myrtenal, myrtenol, carvone, and 1,2-pinanediol [41,42]. α-Pinene oxide is used in organic syntheses as the raw material for obtaining valuable compounds such as campholenic aldehyde, isopinocamphone, p-cymene, trans-sobrerol, and trans-carveol [43].…”
Section: Introductionmentioning
confidence: 99%
“…Various catalysts were used for the oxidation of α-pinene, including titanium-silicate catalysts such as Ti-MCM-41 [53,54], TS-1 [42], and Ti-MMM-2 [55], and transition metal salts such as CuI, CuCl, CuCl 2 , PdCl 2 , and PdBr 2 [56]. Carbonaceous materials obtained from pine cones were also described as catalysts for the oxidation of α-pinene [41].…”
Section: Introductionmentioning
confidence: 99%